1999
DOI: 10.1590/s0034-89101999000400002
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical model of the evolution of virulence in sexually transmitted HIV/AIDS

Abstract: VOLUME 33 NÚMERO 4 AGOSTO 1999© Copyright Faculdade de Saúde Pública da USP. Proibida a reprodução mesmo que parcial sem a devida autorização do Editor Científico. Proibida a utilização de matérias para fins comerciais. All rights reserved. The evolution of virulence in host-parasite relationships has been the subject of several publications. In the case of HIV virulence, some authors suggest that the evolution of HIV virulence correlates with the rate of acquisition of new sexual partners. In contrast some ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Observing virulence dynamics in the wild is far more difficult. There has been a decade and a half of debate over the expected trajectory of virulence evolution in HIV (Ewald 1991;Bonhoeffer & Nowak 1994;Lipsitch & Nowak 1995;Massad 1996;Lipsitch 1997;Coutinho et al 1999;Levin et al 2001;Courgnaud et al 2004). While recent studies suggest that subtypes with lower fitness now dominate, the empirical evidence on the trajectory of virulence is still somewhat ambiguous (Ariën et al 2005(Ariën et al , 2007Mü ller et al 2006Mü ller et al , 2009Herbeck et al 2008)-perhaps not surprising given the complexity of HIV, which has multiple subtypes, inhabiting many genotypes of hosts, multiple tissue types, and with hugely variable ecological and evolutionary pressures at different stages of infection of a single host.…”
Section: Implications For Virulence Evolution Theorymentioning
confidence: 99%
“…Observing virulence dynamics in the wild is far more difficult. There has been a decade and a half of debate over the expected trajectory of virulence evolution in HIV (Ewald 1991;Bonhoeffer & Nowak 1994;Lipsitch & Nowak 1995;Massad 1996;Lipsitch 1997;Coutinho et al 1999;Levin et al 2001;Courgnaud et al 2004). While recent studies suggest that subtypes with lower fitness now dominate, the empirical evidence on the trajectory of virulence is still somewhat ambiguous (Ariën et al 2005(Ariën et al , 2007Mü ller et al 2006Mü ller et al , 2009Herbeck et al 2008)-perhaps not surprising given the complexity of HIV, which has multiple subtypes, inhabiting many genotypes of hosts, multiple tissue types, and with hugely variable ecological and evolutionary pressures at different stages of infection of a single host.…”
Section: Implications For Virulence Evolution Theorymentioning
confidence: 99%
“…The simplest case of the dynamics of infectious disease is the so-called susceptible-infected-susceptible (SIS) model (Coutinho et al, 1999;Lopez et al, 1999;Massad et al, 1995;Struschiner et al, 1999). In this model, susceptible individuals can become infected if they have one infective contact with any infected individual.…”
Section: A Canine Rabies Model Based On Gradual Rulesmentioning
confidence: 99%
“…This may cause a tremendous amount of imprecision and uncertainty in the interpretation of effect measures in analysis. Furthermore, in general, mathematical functions that are able to describe the epidemiological variables correlation are not available (Coutinho et al, 1999;Lopez et al, 1999;Massad et al, 1995Massad et al, , 2001. Our own experience in dealing with epidemiology and fuzzy epidemic modelling have demonstrated that in the case of biological, and particularly epidemiological models, it is often hard to find functional information about the dynamics of the systems.…”
Section: Introductionmentioning
confidence: 99%
“…This relative contribution may have important consequences to the epidemiological pattern of HIV transmission, as well as to the assessment of the impact of HIV treatment on the epidemiology of HIV/AIDS. In addition, it should be expected that differences in the probability of transmission in each of the distinct phases of the infection may also have important consequences on the evolution of HIV virulence [4].…”
Section: Introductionmentioning
confidence: 99%